2016
DOI: 10.1037/stl0000060
|View full text |Cite
|
Sign up to set email alerts
|

The mind that wanders: Challenges and potential benefits of mind wandering in education.

Abstract: Our minds naturally wander for much of our daily lives. Here we review how mind wandering, or task-unrelated thought, impacts comprehension during lectures and reading, and how it relates to general academic success. In some situations, mind wandering may not hinder performance, and may even aid in creativity, future planning, problem solving, and relief from boredom. We distill research on the negative and potentially positive effects of mind wandering to suggest ways that teachers can reduce and redirect min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…We found that participants’ thoughts were more constrained in the morning and gradually became more freely moving across the beginning of the day, peaking around noon, before falling in the afternoon and then rising again in the evening. These findings provide initial support for the idea that mind-wandering dynamically fluctuates in our everyday lives, which is important given its relationship to educational outcomes (Mills, Graesser, Risko, & D’Mello, 2017; Mrazek et al, 2017; Pachai, Acai, LoGiudice, & Kim, 2016; Seli, Wammes, Risko, & Smilek, 2016; Sousa, Carriere, & eSmilek, 2013; Valdez et al, 2014) and workplace productivity (Dane, 2011; Dust, 2015; Hyland, Lee, & Mills, 2015).…”
Section: Discussionmentioning
confidence: 54%
“…We found that participants’ thoughts were more constrained in the morning and gradually became more freely moving across the beginning of the day, peaking around noon, before falling in the afternoon and then rising again in the evening. These findings provide initial support for the idea that mind-wandering dynamically fluctuates in our everyday lives, which is important given its relationship to educational outcomes (Mills, Graesser, Risko, & D’Mello, 2017; Mrazek et al, 2017; Pachai, Acai, LoGiudice, & Kim, 2016; Seli, Wammes, Risko, & Smilek, 2016; Sousa, Carriere, & eSmilek, 2013; Valdez et al, 2014) and workplace productivity (Dane, 2011; Dust, 2015; Hyland, Lee, & Mills, 2015).…”
Section: Discussionmentioning
confidence: 54%
“…In the attempt to understand the complex relations between MW and learning, studies have mainly focused on the negative effects of MW on the encoding of incoming information from the environment and its direct impact on students’ comprehension during reading (Pachai et al ., ; Smallwood et al ., ). During reading, our mind may unintentionally wander, while our eyes continue to scan the words without paying attention to their meaning, thus disrupting the comprehension of what is currently read (Smallwood, ; Smallwood et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MW has been associated with dysfunctional consequences such as increased unhappiness (e.g., Killingsworth & Gilbert, ), poor performance in sustained attention tasks (Cheyne, Solman, Carriere, & Smilek, ; Mrazek et al ., ; Smallwood et al ., ), or reading (Franklin, Smallwood, & Schooler, ; McVay & Kane, ; Reichle, Reineberg, & Schooler, ; Smallwood, McSpadden, & Schooler, ; Smilek, Carriere, & Cheyne, ). Moreover, MW has been associated with worse performance on measures of fluid intelligence and working memory (Mrazek et al ., ), potentially leading to serious consequences, such as scholastic failure (Lindquist & McLean, ; Pachai, Acai, LoGiudice, & Kim, ; Smallwood, Fishman, & Schooler, ; Storm & Bui, ). The latter is exacerbated by the fact that youth and late adolescents seem to be more vulnerable to the intrusion of MW compared to older adults (e.g., Giambra, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that mindfulness and mind wandering seem to be opposing constructs for the ability to remain undisturbed, it has become a current focus to examine whether mindfulness training can reduce mental wandering. First, contrary to mindfulness, mind wandering requires the ability to avoid distractions, characterized by the interruption of task focus (TUT) (Mooneyham & Schooler, 2016;Pachai et al, 2016;Wu et al, 2016;Zanesco et al, 2016).…”
Section: Mindfulness Training Interventions For Mind Wanderingmentioning
confidence: 99%